Mitigating corruption in the Philippines through holistic governance? - Buendia, Rizal G. (Philippine Journal of Public Administration; Vol 67 (2023), 2023)
This article is a discourse on holistic governance and its prospect of mitigating corruption in the Philippines. It presents the key concept and framework of holistic governance and the key issues it addresses. The critical issues confronting the Philippine bureaucracy are likewise examined in line with the parameters of good and effective governance defined by international development agencies. The study focuses on the vital question of corruption that has historically plagued Philippine governance. Through holistic governance, the paper champions institutional, administrative, and cultural change on how the public sector needs to work differently. Although the Philippines has been used as a case, holistic governance may be adopted by other countries in building up effective governance and reducing the threats of corruption.